DISPERSION OF H2S FROM GEOTHERMAL POWERPLANT IN THE DRY AND RAINY SEASONS IN COMPLEX TERRAIN AREA - Solya Difica Simangunsong, Martina
Potency of geothermal that exist in Sukabumi, West Java, used by PT. X as a powerplant. But there must be side effect from taking the gaseous through injection well. Fluids from inside of the earth brings many compounds of gaseous, include H2S and NH3. Emition of H2S and NH3 from the geothermal plant industry will be dispersed to the atmosphere with the contribution of meteorology. The main influence from that pollutants to the human are nose and respiratory iritation.The distribution of H2S and NH3 was modeled by AERMOD software. This software need preprocessors AERMAP and AERMET to generates output. AERMET processes meteorological data and AERMAP processes elevation and contour of study area. Data meteorology that needed in this modeling are wind direction, wind velocity, relative humidity, precipitation, ceiling height, cloud cover, air pressure, and solar radiation. This model was made with annual and seasonal scenes (rainy and dry season) with averaging time 24-hour, 8-hour, and 1-hour. The results of this model showed that the maximum concentration of H2S located not too far from the cooling tower. The maximum concentration with maximum flowrate in large domain (24-hours|8-hours|1-hours) are (0.212|0.622|2.351) for H2S and (0.037|0.107|0.395) for NH3. Beside that, the model also showed the different results between dry and rainy season. This was because meteorology factors and contour of study area could affect the dispersion of H2S and NH3.